“Gold … Was Certainly Very Attractive; But He Did Not Like New South Wales as a Country in Which to Live.” The Representation of Australian Society in Trollope’s John Caldigate - Setecka, Agnieszka (Studia Anglica Posnaniensia, 2017)
Australia features in numerous Victorian novels either as a place of exile or a land of new opportunities, perhaps the most memorable image of the country having been presented in Charles Dickens’s Great Expectations (1861). Anthony Trollope’s writing, however, offers a much more extensive and complex presentation of Australian life as seen by a Victorian English gentleman. In his Australian fictions, including Harry Heathcote of Gangoil (1874), Catherine Carmichael (1878), and John Caldigate (1879), he presents Australia both as a land of new opportunities and as a place where social hierarchy as it is known in England is upturned and social boundaries either disregarded or drawn along different lines. The present article is concerned with the ways in which Trollope’s John Caldigate represents differences in the structure of English and Australian society, stressing the latter’s lack of a clear class hierarchy characteristic of social organisation “back home”. The society of Australia is presented as extremely plastic and mobile - both in terms of space and structure. Consequently, it can hardly be contained within a stiffly defined hierarchy, and it seems to defy the rules of social organisation that are accepted as natural and obvious in England. In Trollope’s fiction success in Australia depends to a large extent on hard work, ability to withstand the hardships of life with no luxuries, and thrift, and thus on personal virtues, but the author nevertheless suggests that it is defined solely by economic capital at the cost of cultural capital, so significant in England.